Hear or Not to Hear: A Comparative Analysis of Jurisdiction of the Courts in E-commerce Disputes - Sarabdeen, Jawahitha (Journal of Ecohumanism, 2025)
The borderless nature of e-commerce brought opportunities and challenges for businesses and consumers. One of the challenges faced by consumers is finding the right court that has jurisdiction to hear and decide disputes in a transaction or any of their online activities. For a court to recognize a legal right, it must establish jurisdiction over the parties and subject matter. The jurisdiction of a court in a dispute is traditionally decided on the presence of the parties in each jurisdiction or agreement to submit to the jurisdiction. The existing procedural law in many counties has restrictions on bringing a foreign party to a local court or enforcing a local judgment on a defendant in a foreign country. Hence, the article was an attempt to investigate the availability of the laws in the UK, Australia, and Malaysia to address the jurisdiction of the court to hear e-commerce disputes involving foreign entities. The research applying a systematic review of literature, legal content analysis, and comparative legal analysis found that there was a gap in the literature to address the issue of jurisdiction of the courts in hearing and deciding against a foreign e-commerce site. It further revealed that the laws in the UK are satisfactory to bring a foreign defendant to the local jurisdiction in cases of consumer issues, however, enforcement of the judgment beyond the UK is subjected to a reciprocal agreement. In Australia and Malaysia, the laws and regulations are very restrictive and need an amendment to allow e-consumers to successfully bring an action against an e-commerce site and enforce the judgment in a foreign country. The research contributed to filling the gap in the literature and provided suggestions to improve the law on the jurisdiction of the local court to hear and decide cases involving foreign e-commerce defendants.